Preserved ratio impaired spirometry, airflow obstruction, and their trajectories in relationship to chronic kidney disease: a prospective cohort study - Ikramulhaq Patel; JingYan Zhang; YinHe Chai; YuShun Qiao; HongJian Gong; Hui Xu; JianBo Zhou (Scientific Reports)
Abstract Spirometry findings, such as restrictive spirometry and airflow obstruction, are associated with renal outcomes. Effects of spirometry findings such as preserved ratio impaired spirometry (PRISm) and its trajectories on renal outcomes are unclear. This study aimed to investigate the impact of baseline and trajectories of spirometry findings on future chronic kidney disease (CKD) events. This UK Biobank cohort study included participants with CKD who underwent spirometry at baseline (2006–2010). Lung function trajectories were determined using baseline and follow-up spirometry (2014–2020). Cox proportional hazards multivariate regression analysis was used to analyze the association between lung function and the incident CKD. In the baseline analysis (n = 282,354), fully adjusted hazard ratios (HRs) for PRISm participants (vs. normal spirometry) were 1.20 (1.07–1.34) for CKD and 1.51 (1.04–2.19) for end-stage renal disease (ESRD). Over an average 13.8-year follow-up period, 789 participants developed CKD. Trajectory analysis revealed higher CKD incidence with persistent AO (HR = 1.47(1.03–2.12)) and PRISm (HR = 1.28(0.88–1.88)) compared to normal lung function. Transitioning from AO to PRISm was associated with lower CKD incidence (HR = 0.27(0.08–0.93)). Recovery of normal lung function from AO could avert 16% of CKD cases. Our study indicated that baseline PRISm and airflow obstruction are associated with higher risk of incident CKD. Moreover, those with persistent AO findings had a higher risk of CKD incidence. These findings underscore the complex link between spirometry findings and renal outcomes and highlight the importance of considering respiratory and renal health in clinical assessments.